Pengelolaan Barang Alat Tulis Kantor Di Rumah Sakit Bhayangkara Tk. II Sartika Asih Bandung: Overview of Receipt, Storage, and Disbursement of Goods (Office Stationery) at Bhayangkara Tk. II Sartika Asih Bandung - Dian Ekawati; Widawati; Rangga Putra Pratama (Bachelor of Hospital Administration, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Introduction: One effort to maximize hospital functions is to improve administrative services to support other services. Administrative services require office stationery (ATK). Research explains that there is a relationship between the procurement of office stationery and service quality. So it is necessary to manage office stationery properly. Research objective: To describe the process of receiving, storing and dispensing office stationery at Bhayangkara Tk II Sartika Asih Bandung (RSBSA). Research method: This research is descriptive observational quantitative research. The research location is in the RSBSA (office stationery) warehouse. Data collection techniques use observation and interviews. Research Results: The process of receiving goods (office stationery) at the RSBSA warehouse has been checked and it is in accordance with what was submitted. The process of storing goods (office stationery) in the RSBSA warehouse uses the FIFO and FEFO methods although the storage activities are not neatly organized. Implementation of the process of releasing goods (office stationery) at the RSBSA warehouse has included filling in goods request receipts, checking goods in the warehouse, sending goods according to goods request receipts (office stationery), planning goods to be issued according to unit needs, recording in the expedition book, taking notes reducing items on the stock card and entering data as comparison material. Conclusion: receiving, storing and releasing goods (office stationery) at the Bhayangkara Tk II Sartika Asih Bandung Hospital has been carried out according to the flow